Impact of Magnetic Field on Dose Distribution in MR-Guided Radiotherapy of Head and Neck Cancer - Xia, Wenlong; Zhang, Ke; Li, Minghui; Tian, Yuan; Men, Kuo; Wang, Jingbo; Yi, Junlin; Li, Yexiong; Dai, Jianrong (Frontiers in Oncology, 2020)
Purpose: This study investigates the impact of magnetic field on plan quality and dose at the tissue-air interface in MR-guided radiotherapy of head and neck cancer. Materials and methods: The charts of 10 patients with hypopharyngeal carcinoma who were treated with conventional fractionated radiotherapy were collected and reviewed. The skin and tissues containing air cavities were contoured. Three plans using 9 fields intensity modulated radiation therapy were generated for each patient in the Monaco treatment planning system (TPS) of an Elekta Unity MR-linac. The first plan was optimized without magnetic field (plan0T). The second plan was re-calculated in presence of a 1.5 T magnetic field (plan1.5T_reCal) using the same segment shape and monitor units as the first plan. The third plan was re-optimized in presence of a 1.5 T magnetic field (plan1.5T_reOpt) using the same cost function as the first plan. The dose to the skin and tissues containing air cavities were compared across the three types of plans. A plan quality metric method was used to evaluate the plan quality according to the clinical requirements. Results: The skin dose was increased in the presence of the 1.5 T magnetic field, and the amplitude increase of plan1.5T_reOpt (ΔDmean 1.30 ± 0.42 Gy, ΔDmax 1.68 ± 1.36 Gy) was smaller than that of plan1.5T_reCal (ΔDmean 1.81 ± 0.79 Gy, ΔDmax 5.43 ± 2.26 Gy). There were no significant differences in terms of the metrics of interfaces of tissues containing air cavities, except for an increased maximum dose to the larynx and trachea. The plan quality of plan1.5T_reCal (68.0 ± 9.2) was significantly worse than that of plan0T (82.2 ± 7.0), and the plan quality of plan1.5T_reOpt (80.0 ± 7.0) was similar to that of plan0T. Conclusion: The presence of a 1.5 T magnetic field had an apparent impact on the dose distribution, especially a significant increase in the skin dose. The plan quality of plan1.5T_reOpt was similar to that of the original plan0T when the same cost function was used.